Ambiguity on Audits and Cooperation in a Public Goods Game - Zhixin Dai; Robin M. Hogarth; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2014)
We investigate the impact of various audit schemes on the future provision of public goods, when contributing less than the average of the group is sanctioned exogenously and the probability of an audit is unknown. We study how individuals update their beliefs about the probability of being audited, both before and after audits are definitely withdrawn. We find that when individuals have initially experienced systematic audits, they decrease both their beliefs and their contributions almost immediately after audits are withdrawn. In contrast, when audits were initially less frequent and more irregular, they maintain high beliefs about the probability of being audited and continue cooperating long after audits have been withdrawn. Inconsistency in experiencing audits across time clearly increases the difficulty of learning the true audit probabilities. Thus, conducting less frequent and irregular audits with higher fines can increase efficiency dramatically.
Keywords: C92; H41; D83; 330; ambiguity; audits; sanctions; beliefs; cooperation; public goods; experiment